Optimism and Problem-Focused Coping on Students during The COVID-19 Pandemic - Safrilsyah, Safrilsyah; Zuhra, Fatimah; Barmawi, Barmawi; Fatmawati, Fatmawati; Mohd Yusoff, Mohd; Ibrahim, Ibrahim (UIN Sunan Kalijaga, 2022)
The purpose of this research is to explore the influence of optimism on the problem-focused coping of students at Ar-Raniry State Islamic University and to find out the difference in optimism and problem-focused coping between male and female students. Data were collected from 320 students (81 male and 239 female) using a proportional stratified sampling. Data were collected by using two questionnaires, (1) Optimism by using the scale of optimism (Seligman, 2008) and (2) Problem-focused coping by using the Coping scale (Lazarus, 1984). Data were analyzed descriptively, and statistical analysis (hypothesis testing) was done using a simple regression procedure under SPSS/PC Ver.23.00. This study's results indicated a significant positive correlation between optimism and problem-focused coping among students. The respective R-square is 0.166, a result of the coefficient is 0.407. There are no significant differences in problem-focused coping and optimism among students. However, there are significant gender differences, male students are more problem-focused with coping and optimism than female students. Penelitian ini bertujuan untuk mengetahui pengaruh optimisme terhadap problem focused coping mahasiswa Universitas Islam Negeri Ar-Raniry Banda Aceh dan mengtahui perbedaan optimisme dan problem focused coping diantara mahasiswa laki-laki dan perempuan. Sampel penelitian ini berjumlah 320 mahasiswa (81 laki-laki dan 239 perempuan) dengan menggunakan proporsional stratified sampling. Pengumpulan data dilakukan dengan menggunakan dua kuesioner, (1) Optimisme dengan menggunakan skala optimisme (Seligman, 2008) dan (2) Problem focused coping dengan menggunakan skala Coping Data dianalisis secara deskriptif dan analisis statistik (pengujian hipotesis) dilakukan dengan prosedur simple Regression. Hasil penelitian ini menunjukkan bahwa terdapat hubungan positif yang signifikan antara optimisme dengan problem focused coping pada siswa. R-square adalah 0,166, hasil koefisien adalah 0,407. Tidak ada perbedaan yang signifikan dari problem focused coping di kalangan mahasiswa, tetapi ada perbedaan yang signifikan dari jenis kelamin, bahwa laki-laki lebih tinggi problem focused coping dan sikap optimisme daripada mahasiswa perempuan.